O-012 Anti-thrombogenic coating for flow diverters: using high-frequency optical coherence tomography to image acute thrombus burden. (22nd July 2019) - King, R; Langan, E; Marosfoi, M; Ughi, G; Raskett, C; Gounis, M
Abstract : Introduction: The use of stents in the treatment of wide neck aneurysms, and more recently the adoption of flow diverters, are important tools for the treatment of aneurysms. 1 One major complication of such implants is thromboembolism, requiring the use of dual anti-platelet therapy (DAPT). However, due to variable response and inherent risks of DAPT, new stents are being developed with anti-thrombogenic coatings with the goal to reduce or eliminate the need for DAPT. Methods: A novel hydrophilic polymer coating (HPC) applied to a nitinol substrate has been shown to resist platelet aggregation in vitro. 2 We sought to demonstrate preliminary evidence to confirm this observation in vivo. Three pigs were used with different regimens: no antiplatelet medication (NAPT), 81 mg aspirin (SAPT), and 81 mg aspirin with 75 mg Clopidogrel (DAPT). Two control and two coated devices were implanted in each animal. High Frequency Optical Coherence Tomography (HF-OCT), with a spatial resolution approaching 10 microns, was used to study acute thrombus formation along the surface of the device. HF-OCT acquisitions were acquired 20 minutes following device implant. Specifically, the total clot volume on each side branch opening (SBO) was segmented with manual input by a blinded user. Statistical analyses were performed to determine the relative benefit of the HPC coating and the antiplatelet regiment for prevention of platelet aggregation, a linear model was constructed to interrogate the relative importance. Results: The figure 1 shows one section from each device type. It was found that device type and aspirin where significantly correlated with thrombus volume over SBOs. Mean thrombus volume per mm 2 of SBO for coated versus control devices was 0.00033 mm versus 0.087 mm, respectively (p = 0.005). Mean clot per SBO was 0.004 mm versus 0.15 mm in animals receiving aspirin versus NAPT (p<0.001). The linear model found that mean thrombus (0.222 mm) was dramatically reduced by the HPC coating (coefficient = -0.221), aspirin use (coefficient = -0.214), and that the combined effect removed nearly all clot. Conclusions: This preliminary evidence shows the dramatic effect that the coating can have on the acute thrombus formation. Further, this novel HF-OCT technology allows for quantitative measurements of the amount of thrombus formed on the surface of a flow diverter, not just the presence. Finally, this study shows the possibility that the combined effect of aspirin and this new coating may be sufficient antiplatelet therapy. References: Neurosurgery 2017;80:40–48. CardioVasc Intervent Radiol 2018;41:1779–1785. Disclosures: R. King: None. E. Langan: None. M. Marosfoi: None. G. Ughi: 4; C; Gentuity LLC. 5; C; Gentuity LLC. C. Raskett: None. M. Gounis: 2; C; Phenox